2006
DOI: 10.1111/j.1466-8238.2006.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a connection between weather at departure sites, onset of migration and timing of soaring‐bird autumn migration in Israel?

Abstract: Aims Different aspects of soaring-bird migration are influenced by weather. However, the relationship between weather and the onset of soaring-bird migration, particularly in autumn, is not clear. Although long-term migration counts are often unavailable near the breeding areas of many soaring birds in the western Palaearctic, soaring-bird migration has been systematically monitored in Israel, a region where populations from large geographical areas converge. This study tests several fundamental hypotheses reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 27 publications
(29 reference statements)
1
27
0
Order By: Relevance
“…The arrival of fair weather after prolonged periods of suboptimal flight conditions, on the other hand, can spur mass migration events. This is true at geographical bottlenecks and leading lines for migrant birds as well as more inland migration sites (Allen et al 1996; Shamoun-Baranes et al 2006). The ability to predict migration fluxes of a range of nocturnal migrants based on local weather (Erni et al 2002; van Belle et al 2007) strongly supports the proposition that birds will have similar responses to weather within certain periods of time and parts of a flyway (Farnsworth et al 2016).…”
Section: Population and Migration System Level Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The arrival of fair weather after prolonged periods of suboptimal flight conditions, on the other hand, can spur mass migration events. This is true at geographical bottlenecks and leading lines for migrant birds as well as more inland migration sites (Allen et al 1996; Shamoun-Baranes et al 2006). The ability to predict migration fluxes of a range of nocturnal migrants based on local weather (Erni et al 2002; van Belle et al 2007) strongly supports the proposition that birds will have similar responses to weather within certain periods of time and parts of a flyway (Farnsworth et al 2016).…”
Section: Population and Migration System Level Consequencesmentioning
confidence: 99%
“…1). While visual observations may have a restricted spatial extent, constant effort sites and observation networks created opportunities for long-term studies and enabled researchers to identify recurring patterns of migration and elucidate how birds respond to weather (Allen et al 1996; Maransky et al 1997; Shamoun-Baranes et al 2006). In recent decades new measurement and modelling techniques have greatly facilitated studying how birds respond to weather and what the consequences are for individuals or populations, facilitating a new age of research and discovery (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric conditions are known to influence the onset of migration (Shamoun-Baranes et al 2006; Gill et al 2009), migration phenology (Hüppop and Hüppop 2003; Jonzen et al 2006; Bauer et al 2008), stopover decisions (Åkesson and Hedenström 2000; Dänhardt and Lindström 2001; Schaub et al 2004; Wikelski et al 2006; Brattström et al 2008), flight speeds (Garland and Davis 2002; Shamoun-Baranes et al 2003a; Kemp et al in review), flight altitudes (Bruderer et al 1995; Wood et al 2006, 2010; Reynolds et al 2009; Schmaljohann et al 2009), flight strategy (Gibo and Pallett 1979; Pennycuick et al 1979; Gibo 1981; Spaar and Bruderer 1997; Spaar et al 1998; Sapir 2009), orientation and trajectories (Thorup et al 2003; Chapman et al 2008; Srygley and Dudley 2008; Chapman et al 2010), migration intensity or probability (Erni et al 2002; Reynolds 2006; Cryan and Brown 2007; Stefanescu et al 2007; van Belle et al 2007; Leskinen et al 2009), as well as migratory success (Erni et al 2005; Reilly and Reilly 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This could be an indication that birds use atmospheric pressure as a trigger to either stay or to initiate migratory flight activity on a daily basis. Dänhardt and Lindström (2001) and Shamoun-Baranes et al (2006) also suggested that atmospheric pressure may function as an external trigger for migratory birds to start their migratory journey in the wild. As mentioned above, atmospheric pressure seems to be a good predictor for future weather conditions, and garden warblers might therefore rely mainly on this meteorological parameter when deciding whether to migrate or not.…”
Section: Discussionmentioning
confidence: 99%
“…Liechti 2006), (2) observation counts of free flying birds (e.g. Marra et al 2005;Shamoun-Baranes et al 2006;Sokolov and Gordienko 2008), (3) radio-tracking (e.g. Å kesson and Hedenström 2000; Bolshakov and Chernetsov 2004), (4) ringing recoveries (e.g.…”
Section: Introductionmentioning
confidence: 99%